Analisis Minat Masyarakat Kelurahan Langkapura Baru terhadap Pembelian Produk Daging Ayam Ras (Broiler Chicken) di Pasar Tradisional dan Modern - D Arman; N Irwani; R Noviadi (PETERPAN (Jurnal Peternakan Terapan), 2022)
This study aims to analyze the public interest in Langkapura Baru Village towards purchasing broiler chicken products in traditional and modern markets. In the Langkapura Baru Village area, Bandar Lampung. The research was conducted using a qualitative descriptive method. The technique used in this research is a case study technique. This study collects various data sources including primary data and secondary data. Primary data is data that is directly obtained from information from respondents from the Langkapura Baru Village community which is carried out by means of observation and filling out questionnaires. Secondary data is data obtained from various literacy that helps support the processing of data from the observed variables. Based on the results and discussion, the analysis of the people of Langkapura Baru Village on the purchase of broiler meat products in traditional and modern markets, it can be concluded that, people prefer to buy purebred chicken meat products in modern markets with better product considerations, prices that match the product. , active promotion, and strategic place..